2021
DOI: 10.5535/arm.21068
|View full text |Cite
|
Sign up to set email alerts
|

Peak Voluntary Cough Flow and Oropharyngeal Dysphagia as Risk Factors for Pneumonia

Abstract: Objective To investigate the relationship between voluntary peak cough flow (PCF), oropharyngeal dysphagia, and pneumonia in patients who were evaluated with videofluoroscopic swallowing study (VFSS).Methods Patients who underwent both VFSS and PCF measurement on the same day were enrolled retrospectively (n=821). Pneumonia (n=138) and control (n=683) groups were assigned based on presence of pneumonia within 1 month from the date of VFSS assessment. In addition, sex, age (<65 and ≥65 years), preceding cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our main finding was that community-dwelling ambulatory older adults with low RSST had lower PCF, MIP, and MEP values than those without low RSST. This is consistent with the finding of reduced PCF in patients with dysphagia, although many of whom had cognitive or physical impairments were from a different population than the participants in this study 20 ) . Similarly, a previous finding that patients with dysphagia had lower PCF and MEP in head and neck cancer survivors 21 ) supports our finding.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our main finding was that community-dwelling ambulatory older adults with low RSST had lower PCF, MIP, and MEP values than those without low RSST. This is consistent with the finding of reduced PCF in patients with dysphagia, although many of whom had cognitive or physical impairments were from a different population than the participants in this study 20 ) . Similarly, a previous finding that patients with dysphagia had lower PCF and MEP in head and neck cancer survivors 21 ) supports our finding.…”
Section: Discussionsupporting
confidence: 92%
“…PCF (219 L/min) in the low RSST group was 22% lower than the control group. Reduced PCF (<160 L/min) in older adults with dysphagia and poor functional status significantly increases the risk of aspiration pneumonia 20 ) . In this study, all participants were independent in their daily lives, and participants with neurological disease or airflow limitation were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we showed that respiratory function (VC, FVC, and PImax) is associated with peak cough flow (PCF), [22,23] which is used to measure the coughing capacity, and low PCF is associated with the development of pneumonia. [24] Several bedridden older patients, similar to those included in this study, have difficulty in communicating, and measuring their VC, FVC, and PCF is often difficult. Future analyses of the relationship among V T , PCF, and pneumonia in the appropriate reclining wheelchair sitting position may yield the development of programs that can help prevent pneumonia in bedridden older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were instructed to cough after maximal deep inspiration. PCF assessment was performed 3 times, and the highest value was used for analysis [ 18 ].…”
Section: Methodsmentioning
confidence: 99%